Conservation of cultural heritage in Malaysia : a review on national heritage act 2005 / Nurul Huda Rozlan...[et al.] - Rozlan, Nurul Huda; Roslee, Azzahra; Ahmad, Masfufah; Mohd Salleh, Noralia Fathanah (Faculty of Law, 2013)
Malaysia is very fortunate to have many historic buildings which have both the architectural and historical value which are protected in the National Heritage Act 2005. With the rising awareness amongst the public regarding the conservation of our precious national heritage, many historical buildings have been preserved and conserved very well. However, some of them have sadly been converted to become premises for banks, restaurants, offices or even shopping malls. Thus, in December 2005, parliament passed the National Heritage Act which came into force on 1 March 2006. This Act is a replacement of Antiquities Act 1976 and Treasure Trove Act 1957. The passing of this new Act draws the attention of the public as well as local organizations. Some give many credits, inter alia, alleged that the Act is already complete. Despite of the credits, the Act, at the same time, also received a lot of critics from various individuals, groups and organization as it is said to be ineffective and unenforceable. This research paper aims to draw the attention on the flaws or loopholes being purported against this Act and recommendations to overcome the alleged flaws. Among the issues that will be discussed in this research paper include, failure of authorities to observe their power efficiently, loopholes in our laws and lack of appreciation of the value of the heritage. We hope that this research paper will be a reading that will provide a better understanding on this Act